2014
DOI: 10.2965/jwet.2014.469
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of Fecal Indicators in Channels of Johkasou Systems

Abstract: A johkasou system is getting popular as a decentralized wastewater treatment system in low-density communities. Treated waters of the johkasou systems, which are generally discharged into channels within residential areas before entering the local receiving water body, may contain microbial contaminants. To identify the characteristics of fecal indicators in the channels of the johkasou systems, the concentrations of fecal indicators (F-RNA bacteriophages, GIII F-RNA bacteriophages, Escherichia coli, and total… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…Previous studies reported that high concentrations of total coliform and E. coli were recorded in both water and sediment of channels receiving effluents from Johkasou, an advanced onsite domestic system in Japan (Setiyawan et al, 2014). That high concentration of fecal indicators was still observed although during high flow condition which indicates less hydrological influenced on the fecal indicator in rural areas (Jamieson et al, 2003).…”
Section: Introductionmentioning
confidence: 90%
“…Previous studies reported that high concentrations of total coliform and E. coli were recorded in both water and sediment of channels receiving effluents from Johkasou, an advanced onsite domestic system in Japan (Setiyawan et al, 2014). That high concentration of fecal indicators was still observed although during high flow condition which indicates less hydrological influenced on the fecal indicator in rural areas (Jamieson et al, 2003).…”
Section: Introductionmentioning
confidence: 90%
“…Several studies have also highlighted the seasonal differences in the microbiological quality of surface water quality due to numerous factors such as the unequal loading of wastewater, solar irradiation, temperature, water flow, dilution, rainfall, organic matter, and the origin of the microorganisms 15,16) . In the previous study, fecal indicators have been detected in the channels of johkasou systems 17) . However, the seasonal characteristics of fecal indicators in the local water environment receiving johkasou effluents are little known.…”
Section: Introductionmentioning
confidence: 93%
“…The PMMoV titre was assessed in wastewater samples derived from the USA, Germany, New Zealand and Vietnam (Hamza et al, 2011;Kitajima et al, 2014;Kuroda et al, 2015;Rosario et al, 2009;Schmitz et al, 2016;Symonds et al, 2016). FRNAP-II prevalence in wastewater was only assessed in Japan and Ireland (Flannery et al, 2013;Haramoto et al, 2015Haramoto et al, , 2012Lee et al, 2018), while FRNAP-III prevalence in wastewater was only assessed in Japan (Haramoto et al, 2015(Haramoto et al, , 2012Lee et al, 2018;Setiyawan et al, 2014Setiyawan et al, , 2013. In wastewater, the concentrations of phages associated with Bacteroides BG-124 were assessed in the USA, Brazil, the UK (England) and Switzerland (E. Dias et al, 2018a;McMinn et al, 2014;Prado et al, 2018;Purnell et al, 2015;Stefanakis et al, 2019;Wicki et al, 2015), BacRYC 2056P were investigated in Colombia, the UK, Spain, France, Cyprus, Sweden, Switzerland and Thailand (Cost an-Longares et al, 2008;Gomila et al, 2008;Payan et al, 2005;Venegas et al, 2015;Wangkahad et al, 2017;Wicki et al, 2015Wicki et al, , 2011, BacGA17P were found in Colombia and several European countries (Casanovas-Massana et al, 2015;Cost an-Longares et al, 2008;Gomila et al, 2008;Mayer et al, 2016;Payan et al, 2005;Venegas et al, 2015;Wicki et al, 2015) and BacARABA84P was identified in Switzerland...…”
Section: Criterion 3: Presence In Wastewater At High Concentrationsmentioning
confidence: 99%